Deaths of obstructive lung disease in the Yangpu district of Shanghai from 2003 through 2011： a multiple cause analysis - Cheng, Yi; Han, Xue; Luo, Yong; Xu, Weiguo (Chinese medical journal, 2014)
Background Obstructive lung disease （OLD, chronic obstructive pulmonary disease or asthma） is an important cause of death in older people. There has been no exhaustive population-based mortality study of this subject in Shanghai. The objective of this study was to use a multiple cause of death methodology in the analysis of OLD mortality trends in the Yangpu district of Shanghai, from 2003 through 2011. Methods We analyzed death data from the Shanghai Yangpu District Center for Disease Control and Prevention for Medical Cause of Death database, selecting all death certificates for individuals 40 years or older on which OLD was listed as a cause of death. Results From 2003 to 2011, there were 8 775 deaths with OLD listed, of which 6 005 （68%） were identified as the underlying cause of death. For the entire period, a significantly decreasing trend of age standardized rates of death from OLD was observed in men （-6.2% per year） and in women （-5.7% per year）, similar trends were observed in deaths with OLD. The mean annual rates of deaths from OLD per 100 000 were 161.2 for men and 80.8 for women from 2003 to 2011. While, as the underlying cause of death, the main associated causes of death were as follows： cardiovascular diseases （70.7%）, carebrovascular diseases （13.3%）, diabetes （8.6%）, and cancer （4.3%）. The associated causes and the principal overall underlying causes of death were cardiovascular diseases （37.0%）, cancer （30.3%）, and cerebrovascular disease （15.3%）. A significant seasonal variation, with the highest frequency in winter, occurred in deaths identified with underlying causes of chronic bronchitis, other obstructive pulmonary diseases, and asthma. Conclusions Multiple cause mortality analysis provides a more accurate picture than underlying cause of total mortality attributed on death certificates to OLD. The major comorbidities associated with OLD were cardiovascular disease, cancer, and cerebrovascular disease. From 2003 to 2011, the mortality rate from OLD decreased substantially in the Yangpu district of Shanghai.